Climate Governance and Agriculture in Southeast Asia: Learning From a Polycentric Approach - Fasting, Siw; Bacudo, Imelda; Damen, Beau; Dinesh, Dhanush (Frontiers Media, 2021)
The global climate governance framework will need to empower a wide range of groups representing different geopolitical and sector-specific interests to engage in climate action. Learning from polycentric governance approaches could provide insight on how to foster more inclusive engagement and more effective outcomes from global efforts to fight climate change. The Paris Agreement has opened up room for this type of bottom-up, polycentric governance and new attention to important issues such as agriculture. The Association of Southeast Asian Nations Climate Resilience Network (ASEAN-CRN) is an example of a polycentric system to enhance resilience and adapt to climate change. The ASEAN Negotiating Group on Agriculture (ANGA) enables the region’s agriculture sector to shape global climate governance frameworks. The case of ANGA highlights that opening up space for polycentric systems can foster climate action in relevant sectors. Supporting regions to navigate UNFCCC processes can further enable polycentric systems, enhancing climate resilience and adaptation.